Sekolah Sehat Berbasis Kesehatan dan Lingkungan di Sekolah Indonesia Kuala Lumpur Malaysia - Taiyeb, A. Mushawwir; Rauf, Bakhrani; Azizah, Laelah; Sudiadharma, Sudiadharma; Purnamasari, Andi Bida (Program Studi Pendidikan IPA Fakultas MIPA Universitas Negeri Makassar, 2025)
Healthy and clean lifestyle is a process that involves lifestyle changes to improve physical and mental health and maintain the environment around the school to remain clean and healthy. The implementation of health and environmental-based school activities uses a participatory method through interactive discussion activities between the service team and the management and teaching team and mentoring of clean and healthy lifestyles at the Indonesian School Kuala Lumpur continued by cleaning the school environment by involving students. The target of this community service program is the school environment including the Principal, teachers and other teaching teams and the secretary at the Indonesian School Kuala Lumpur Malaysia. After this activity ended, the physical environment of the school was seen to be cleaner and the school intensified the role of teachers and students to jointly maintain a clean lifestyle and order in the school environment.